Risk predictors for the development of retinopathy of prematurity in very low birth weight neonates - Shreetal, Sheena; Sobhakumar, S; Rhiju, Reshmi; Nair, Shreetal Rajan (Indian Journal of Child Health, 2016)
Background: Retinopathy of prematurity (ROP) is an important cause of visual and neurological impairment in premature infants. Identification of risk factors and effective management of the same will help in better outcomes. Information on ROP and its risk factors are limited especially from South India and interventions directed at prevention and treatments have produced only modest results. Methods: The study was of a prospective, unmatched case–control design and was conducted in premature, very low birth weight infants (<34 weeks; <1500 g) admitted to Neonatal Intensive Care Unit in a tertiary care center in South India during an 18-month period. The neonates were screened for ROP and subjects who developed ROP were classified as cases and those who did not were categorized as controls. The maternal risk factors studied were the type of delivery, maternal fever, pregnancy-induced hypertension (PIH), gestational diabetes mellitus, cardiac disease, premature rupture of membrane, antepartum hemorrhage, chorioamnionitis, multiple pregnancy, infertility treatment, urinary tract infections, polyhydramnios, and oligohydramnios. The neonatal factors studied were gestational age, birth weight, septicemia, apnea, anemia, hypotension, need for inotropic support, type and duration of oxygen therapy, patent ductus arteriosus, necrotizing enterocolitis, intraventricular hemorrhage, and phototherapy. Both univariate and multivariate analyses were carried out. Results: A total of 54 cases and 54 controls (1:1) were enrolled into the study. Males dominated the study (63% of cases). Univariate analysis showed gestational age, PIH, birth weight, sepsis, oxygen administration, hypotension and packed cell transfusion as important risk factors for ROP. On binary logistic regression analysis, birth weight (odds ratio: 6.00; p: 0.014), oxygen exposure (odds ratio: 11.05; p: 0.003), and hypotension (odds ratio: 6.85; p: 0.009) were identified as important risk predictors of ROP. Conclusions: The study adds important information to the understanding of risk factors of ROP.